(untitled) (Research, Society and Development, 2021)
The SARS-CoV-2 spread and the installation of a pandemic generated drastic changes in society’s lifestyle, in health practices, and in the way we do and consume science. There are countless uncertainties regarding the virus and its health implications, especially for individuals from vulnerable groups, such as oncologic patients. The aim of this systematic review was to identify what has been the reality of oncology in the SARS-CoV-2 pandemic. A systematic review was carried out on the Pubmed® platform, based on the Prisma protocol, using the following keywords were searched: COVID-19 and Cancer. Among the 94 works selected, including systematic reviews, reviews, randomized trials, multicenter studies, meta-analysis, controlled clinical-trials, comparative studies and case reports, only 36 publications corresponded to the purpose of this study and were used. The results showed that, despite the large volume of studies, there is no consensus concerning gold standard measures. As individuals with cancer tend to evolve with more severe conditions when infected with SARS-CoV-2, oncology services have adopted protocols to guarantee adequate management and prevent the spread of the infection onto its facilities. The possible scarcity of resources during the SARS-CoV-2 pandemic brought the necessity to adapt adjust clinical conduct in oncology. Considering the severity and the possibility of a sudden progression of some types of cancer, the professionals must analyze all cases individually to determine the best approach.